Pre‐analytical factors affecting the establishment of a single tube assay for multiparameter liquid biopsy detection in melanoma patients. Issue 5 (4th April 2020) - Schneegans, Svenja; Lück, Lelia; Besler, Katharina; Bluhm, Leonie; Stadler, Julia‐Christina; Staub, Janina; Greinert, Rüdiger; Volkmer, Beate; Kubista, Mikael; Gebhardt, Christoffer; Sartori, Alexander; Irwin, Darryl; et al.
Abstract : The combination of liquid biomarkers from a single blood tube can provide more comprehensive information on tumor development and progression in cancer patients compared to single analysis. Here, we evaluated whether a combined analysis of circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), and circulating cell‐free microRNA (miRNA) in total plasma and extracellular vesicles (EV) from the same blood sample is feasible and how the results are influenced by the choice of different blood tubes. Peripheral blood from 20 stage IV melanoma patients and five healthy donors (HD) was collected in EDTA, Streck, and Transfix tubes. Peripheral blood mononuclear cell fraction was used for CTC analysis, whereas plasma and EV fractions were used for ctDNA mutation and miRNA analysis. Mutations in cell‐free circulating DNA were detected in 67% of patients, with no significant difference between the tubes. CTC was detected in only EDTA blood and only in 15% of patients. miRNA NGS (next‐generation sequencing) results were highly influenced by the collection tubes and could only be performed from EDTA and Streck tubes due to hemolysis in Transfix tubes. No overlap of significantly differentially expressed miRNA (patients versus HD) could be found between the tubes in total plasma, whereas eight miRNA were commonly differentially regulated in the EV fraction. In summary, high‐quality CTCs, ctDNA, and miRNA data from a single blood tube can be obtained. However, the choice of blood collection tubes is a critical pre‐analytical variable. Abstract : We assessed whether a combined analysis of circulating tumor cells, circulating tumor DNA, and microRNA in total plasma or extracellular vesicles from one blood sample is feasible. We show that high‐quality data from a single blood tube can be obtained in melanoma patients. However, the choice of the tube affects the outcome of the analysis, underlining the importance of pre‐analytical factors.